Markovian dynamics of the two-mode bose-einstein condensate - Rajagopal, Kalai Kumar; Umarov, Bakhram; Muniandy, Sithi (2015)
The Mean-field dynamics of atomic condensate loaded in two symmetric traps coupled to a reservoir is studied. In this work we discuss the effect of damping on the boson Josephson junction (BJJ) and the macroscopic quantum self-trapping (MQST) states which are peculiar to the dynamics of the two-mode BEC. We found that damping causes the destruction of quantum self-trapping state and could set in chaos.